Naming the “baby” or the “beast”? The importance of concepts and labels in healthcare safety investigation - Wiig, Siri; Macrae, Carl; Frich, Jan; Øyri, Sina Furnes (Frontiers in Public Health, 2023)
This paper focuses on concepts and labels used in investigation of adverse events in healthcare. The aim is to prompt critical reflection of how different stakeholders frame investigative activity in healthcare and to discuss the implications of the labels we use. We particularly draw attention to issues of investigative content, legal aspects, as well as possible barriers and facilitators to willingly participate, share knowledge, and achieve systemic learning. Our message about investigation concepts and labels is that they matter and influence the quality of investigation, and how these activities may contribute to system learning and change. This message is important for the research community, policy makers, healthcare practitioners, patients, and user representatives.